Recent demographic developments in Ireland - Leser, C. E. V. (Statistical and Social Inquiry Society of Ireland, 1965)
Seen from the demographic point of view, Ireland is well known to possess a number of unusual features m comparison with other countries of the Western world. The effect on natural population increase of a high average age at marriage, together with a high proportion of men and women who never marry at all, was offset by a large family size for married couples, the natural population increase in turn was offset by a high emigration rate, resulting until recent years m a steady decline m population size In the light also of the results of the 1961 Population Census, it seems worthwhile to reassess the demographic position and prospects. All that is attempted is to study some of the salient features of the current position m the fields of deaths, marriages, births, labour force and migration. Comparisons are made with earlier dates, though no attempt is made to go back further than 1926,which is the year of the first Population Census in the Free State.
Read before the Society, 28 May 1965
Keywords: Demographics; Population; Fertility; 314.15